Tumor-Associated Release of Prostatic Cells into the Blood after Transrectal Ultrasound-Guided Biopsy in Patients with Histologically Confirmed Prostate Cancer. (30th December 2019) - Joosse, Simon A; Beyer, Burkhard; Gasch, Christin; Nastały, Paulina; Kuske, Andra; Isbarn, Hendrik; Horst, Ludwig J; Hille, Claudia; Gorges, Tobias M; Cayrefourcq, Laure; Alix-Panabières, Catherine; Tennstedt, Pierre; et al.
Abstract: BACKGROUND: Transrectal ultrasound-guided prostate biopsy (TRUS) is a standard procedure for prostate cancer diagnosis. Because prostate cancer is a multifocal disease in many patients, multiple sampling (n ≥ 10) is required, which may bear the risk of systemic spread of cancer cells. DESIGN: Using the standardized CellSearch ® system that allows for the detection of single epithelial cell adhesion molecule-positive circulating tumor cells (CTCs) in blood, we investigated whether prostate biopsy is associated with release of prostatic tumor cells into the circulation. Peripheral blood was obtained before and within 30 min after performing prostate biopsy from 115 men with increased serum prostate-specific antigen. RESULTS: The number of CTCs significantly increased after biopsy in men with histologically confirmed prostate cancer (odds ratio, 7.8; 95% CI, 4.8–12.8), whereas no biopsy-related changes could be detected in men without confirmed prostate cancer. Multivariable analysis showed that biopsy-related increase of CTCs was significantly correlated with a worse progression-free survival (hazard ratio, 12.4; 95% CI, 3.2–48.6) within the median follow-up of 41 months. CONCLUSIONS: Prostate biopsies may lead to a tumor-associated release of CTCs into the blood circulation. Larger confirmatory trials with longer follow-up periods are required before any change in clinical practice can be recommended.